Enhancing Social Media Content Management in a Public Service Institution through Collaborative Community Service - Muhammad Ashdaq; Nur Fitriayu Mandasari; Valentino Aris; Muhammad Taufik; Andi Ruslan (PT. Global Research Collaboration, 2025)
This community engagement initiative was carried out through collaboration between a religious service organization responsible for pilgrimage operations and faculty members from a digital business study program at a public university. The program was motivated by the organization’s challenges in managing its social media content, which included unstructured information flow, inconsistent distribution, and suboptimal visual design. The intervention involved a structured mentoring process covering content documentation, content creation, and news script development. The results demonstrated a noticeable improvement in social media engagement, reflected in higher interaction and responsiveness from the audience. Indirectly, the activity also enhanced the quality of service delivery by ensuring that information for the families of pilgrims was communicated more quickly, clearly, and reliably. These outcomes highlight the value of collaborative capacity-building in digital communication for public and religious service organizations. The study contributes practical insights into how community-based interventions can strengthen digital media strategies to support transparency, trust, and service quality in the era of digital information.